One Two Three Infinity : Facts & Speculations of Science - George Gamow (Dover Publications Inc., 1988)
Nuclear physicist George Gamow takes the reader on an expedition through the problems, pleasures and puzzles of modern science. Among the topics scrutinized are the macrocosm and the microcosm, theory of numbers, relativity of space and time, entropy, genes, atomic structure, nuclear fission, and the origin of the solar system. In the pages of this book readers grapple with such crucial matters as whether it is possible to bend space, why a rocket shrinks, the "end of the world problem," excursions in the fourth dimension and a host of other topics.